Effect of smoking cessation on the anxiety and the urge for smoking - Demirezen, Murat; Kurçer, Mehmet Ali (Journal of Dependence, 2017)
Objective: Research into the comorbidity between emotional psychopathology and cigarette smoking has often focused upon anxiety. The aim of this study is to show the effect of smoking cessation on anxiety and the desire for smoking.The aim of this study is to show the effect of smoking cessation on anxiety and the desire for smoking.Method: In this experimental design, the voluntary sociodemographic data form, FNBT, Smoking Desire Inventory of Turkish (QSU) version and Hospital AnxietyDepression Scale (HAD) scale were asked to leave the smoking. The first day was applied after three hours of deprivation. Smoking cessation treatment was started between the 8.-10. days. After 4 weeks, the patient was called to control and the QSU and HAD scales were repeated.Results: When the relation between smoking desire and anxiety was examined, it was found that the anxiety level of those who had a high desire for smoking was high.Results: The level of anxiety was high in those who had a high desire for smoking. Anxiety scores were found significantly lower than those who could not leave the cigarette at the end of the first month.Conclusion: QSU should be recommended for smoking cessation outpatient clinics.
Keywords: Smoking cessation; Smoking desire; anxiety